Enhancement on gain and bandwidth of 5G rectangular patch antenna by the suppression of surface waves - Nur Haziyah, Binti Mohamad Razali (Universiti Malaysia Sarawak (UNIMAS), 2017)
Nowadays, wireless technologies have a significant impact in development of countries, organizations, and public interest while contributes to others benefit as well. An example of the important components in wireless technologies is an antenna. Thus, the need of high efficiency in their performance in term of gain and radiation efficiency is desired. A frequency of 10 GHz is chosen due to its high frequency and suitable for 5G technology. The antenna is design by using Computer Simulation Technology (CST) Microwave Studio. Furthermore, the implementation of suppression of surface wave technique will lead to enhancement of the antenna gain while improving the bandwidth as well. Three analyses are done to find the best performance of rectangular patch antenna. Type E has the best value of return loss at 10 GHz center frequency which rises from -23.575 dB to -24.433 dB while bandwidth shows an increasing from 0.10353 to 0.13105 which means up to 2.752 %. Lastly, the gain of the antenna rises from 2.466 dB to 3.423 dB.